Great Women Mystery Writers: Classic to Contemporary - Klein, Kathleen Gregory (Greenwood Press, 1994)
A dictionary of over 117 women mystery authors giving details on their lives and their writing habits.
Keywords: Bibliography; Detective and mystery stories, American; Bio-bibliography; American fiction; Bio-bibliography; Detective and mystery stories, American; Bio-bibliography; Women and literature; Bio-bibliography; Women authors, American; Biography; Detective and mystery stories, English; Dictionaries; Dictionaries; Detective and mystery stories, English; Dictionaries; English fiction; Dictionaries; Women authors, English; English-speaking countries; Women authors; dept.eng; faculty_collection